TRAINING NEEDS ASSESSMENT OF POULTRY FARMERS IN TEHSIL FAISALABAD - A. Razzaq; T. Ali; A. Saghir; S. Arshad; A. Cheema (Journal of Animal and Plant Sciences, 2011)
There are a lot of problems faced by poultry farmers regarding rearing, shed management, and disease management knowledge. Hence there is need to find out those areas of poultry faming in which poultry farmers needs to be educated. The study was conducted in tehsil Faisalabad, comprised of 4 towns named as Jinnah town, Madina town, Lyallpur town, and Iqbal town. There are 489 poultry farms in Faisalabad District. The owner of all such poultry farms comprised the population of the study. A simple random sample of 150 poultry farmers were selected. A validated interview schedule was prepared to collect information from the respondents. The data thus collected were analyzed. The top 9 training required areas of layer farming for establishing a poultry farm followed by treatment of CRD, maintaining distance of shed from residential area space for adult bird preparation of room before arrival of chicks, equipment cleaning treatment of food poisoning treatment of pullorum and preventive measure of pullorum. The top 9 training required areas of broiler farming are cleaning shed followed by preventive measures of coccidiosis symptoms of coccisdiosis symptoms of coryza treatment of coccidiosis treatment of coryza vaccination schedule of hydro pericardium preventive measures of gumboro and symptoms of new castle disease. Overwhelming majority agree on regular training of disease management. They also pointed out that Govt. should launch easy loaning scheme for them.
Keywords: Training needs assessment; poultry farmer